Bilateral Serous Retinal Detachment and Uterine Atony in Association with Preeclampsia - Şadıman Kıykaç Altınbaş; Pınar Cenksoy; Ömer Lütfi Tapısız; Emre Hekimoğlu; Orhan Gelişen (Medical Network, 2012)
Retinal detachment is the separation of the neurosensory retina from the underlying retinal pigment epithelium. In pregnancy with hypertensive disorders, it is a very rare complication and usually seen bilaterally. Here, a case of bilateral serous retinal detachment and uterine atony in association with preeclampsia seen in the postpartum period of a term pregnant woman with no history of prior hypertension is presented.